2002
DOI: 10.1191/0748233702th161oa
|View full text |Cite
|
Sign up to set email alerts
|

In vivo ingestion of heavy metal particles of Se, Hg and W by murine macrophages. A study using scanning electron microscopy coupled with X-ray microanalysis

Abstract: Several heavy metals that are currently employed in industry may become polluters of work and natural environments. As particulate matter, heavy metals are suitable for entering the human body through the respiratory and digestive systems. They often end up inside phagocytes; the size of the microscopic particles modulates both their phagocytosis, and the physiology of macrophages. Here we have adopted an experimental model to investigate the ingestion of particles of three industrial heavy metals (Se, Hg, W) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In liver samples of mice that were intraperitoneally injected with the Hg salt alone, we have detected heavy labeling of the erythrocyte surface by Hg-positive particles (Fig. 2), as we have described before [7][8][9][10]. Injection of Se salt alone failed to label the surface of liver erythrocytes with Se-positive particles.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…In liver samples of mice that were intraperitoneally injected with the Hg salt alone, we have detected heavy labeling of the erythrocyte surface by Hg-positive particles (Fig. 2), as we have described before [7][8][9][10]. Injection of Se salt alone failed to label the surface of liver erythrocytes with Se-positive particles.…”
Section: Resultsmentioning
confidence: 53%
“…The protective effect of selenite on the toxicity of Hg in mammals derives from the formation of stable and inert complexes of mercuric selenide, SeHg [4][5][6]. We have used here electron microscopy to investigate the in vivo interaction between Se and Hg since we had previously documented that it is possible to obtain high-resolution identification of Hg particles in tissues and cells by the use of scanning electron microscopy coupled with X-ray microanalysis (SEM-XRM) [7][8][9][10]. The same technical approach was now used for the simultaneous detection of Hg and Se on the surface of mouse erythrocytes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Asterisk indicates significantly different (p < .05) from the mean for the corresponding group of RAW cells exposed to CH 3 Hg-Cys in the presence 140 mM N-methyl-D-glucamine. All Cells Were Exposed to 5 μm CH 3 Hg-Hcy mercury-containing particles by pinocytosis (Cunha et al, 2004: Cherdwongcharoensuk et al, 2002. Several investigators have demonstrated that when certain metal species, including those of mercury, are taken up by monocytes/macrophages, they alter significantly metabolic activity in the cells Noda et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, very little is known about the mechanisms by which mercuric ions gain entry into monocytes and macrophages. There are some data indicating that phagocytic cells can take up mercuric species by endocytosis (Cunha et al, 2004;Cherdwongcharoensuk et al, 2002). However, very little else is known about the mechanisms by which monocyte/macrophages can take up mercuric species.…”
mentioning
confidence: 97%